Performance of Polyvinyl Alcohol and Polypropylene Fibers under Simulated Cementitious Composites Pore Solution - A. R. Krishnaraja; P. Kulanthaivel; P. Ramshankar; Vincent Herald Wilson; Ponnusamy Palanisamy; S. Vivek; V. Sampathkumar; P. Ganeshan; M. C. Sashikkumar; K. Raja; Senthil Kumaran Selvaraj; A. John Rajan; et al. (Advances in Materials Science and Engineering)
The thermal properties of polymer fibers namely polyvinyl alcohol fiber (PVA) and polypropylene fiber (PP) have been taken for study to carry out this present work. Simulated pore solution (SPS) is prepared by using the combination of chemicals NaOH, KOH, and Ca(OH)2 with distilled water to study the effect of C-S-H gel formation on fibers. The fibers are dipped in the solution for 35 days. The thermal properties of raw and SPS-dipped fibers are fetched out by performing various tests such as Fourier transform infrared (FTIR) analysis, thermo gravimetric analysis (TGA), differential scanning calorimetry analysis, and scanning electron microscopy (SEM). On analysis, the thermal properties of SPS-dipped fiber have better properties when compared with raw fiber. In FTIR analysis the first broad peak of both raw and SPS-dipped fibers are observed between 3000 cm−1 to 2800 cm−1 indicating that fibers have strong bond. In TGA analysis noted that the residual mass of raw fiber (77.19%) is higher than SPS-dipped fiber (52.33%) due to the formation of C-S-H gel formation. DSC analysis showed both endothermic and exothermic reaction under N2 atmosphere.